Coexistence conservation: Reconciling threatened species and invasive predators through adaptive ecological and evolutionary approaches. Issue 7 (6th June 2022) - Evans, Maldwyn J.; Weeks, Andrew R.; Scheele, Ben C.; Gordon, Iain J.; Neaves, Linda E.; Andrewartha, Tim A.; Brockett, Brittany; Rapley, Shoshana; Smith, Kiarrah J.; Wilson, Belinda A.; Manning, Adrian D.
Abstract: Invasive predators are responsible for declines in many animal species across the globe. To redress these declines, conservationists have undertaken substantial work to remove invasive predators or mitigate their effects. Yet, the challenges associated with removal of invasive predators mean that most successful conservation programs have been restricted to small islands, enclosures ("safe havens"), or refuge habitats where threatened species can persist. While these approaches have been, and will continue to be, crucial for the survival of many species, in some contexts they may eventually lock in a baseline where native species vulnerable to invasive predators are accepted as permanently absent from the wild (shifting baseline syndrome). We propose an explicit theme in conservation biology termed " coexistence conservation, " that is distinguished by its pursuit of innovative solutions that drive or enable adaptive evolution of threatened species and invasive predators to occur over the long term. We argue evolution has a large role to play but using it to adapt native species to a new environmental order requires a shift in mindset from small, isolated, and short‐term leaps to deliberate, staged steps within a long‐term strategy. A key principle of coexistence conservation is that predation is treated as the threat, rather than the predator, driving a focus on the outcome rather than the agent. Without a long‐term strategy, we face the permanent loss of many species in the wild. Coexistence conservation is a complementary approach to current practice and will play an important role in shifting our current trajectory from continued and rapid invasive predator‐driven defaunation to a world where invasive predators and native prey can coexist. Abstract : (a) The strategic framework within which coexistence conservation can be implemented. (b) Trials allow conservation scientists to test a priori hypotheses in an iterative manner to determine which tactics improve outcomes in an adaptive management framework whilst keeping risk at manageable levels.